Sex Difference of Radiation Response in Occupational and Accidental Exposure - Narendran, Nadia; Luzhna, Lidia; Kovalchuk, Olga (Frontiers in Genetics, 2019)
Ionizing radiation is a well-established cause of deleterious effects on human health. Understanding the risks of radiation exposure is important for the development of protective measures and guidelines. Demographic factors such as age, sex, genetic susceptibility, comorbidities, and various other lifestyle factors influence the radiosensitivity of different subpopulations. Amongst these factors, the influence of sex differences on radiation sensitivity has been given very less attention. In fact, the International Commission on Radiological Protection (ICRP) has based its recommendations on a population average, rather than the data on the radiosensitivity of distinct subpopulations. In this study, we reviewed major human studies on the health risks of radiation exposure and showed that sex-related factors may potentially influence the long-term response to radiation exposure. Available data suggest that long-term radiosensitivity in women is higher than that in men who receive a comparable dose of radiation. The report on the Biological Effects of Ionizing Radiation (BEIR VII) published in 2006 by the National Academy of Sciences, USA emphasized that women may be at significantly greater risk of suffering and dying from radiation-induced cancer than men exposed to the same dose of radiation. We show that radiation effects are sex-specific, and long-term radiosensitivity in females is higher than that in males. We also discuss the radiation effects as a function of age. In the future, more systematic studies are needed to elucidate the sex differences in radiation responses across the life continuum—from preconception through childhood, adulthood, and old age—to ensure that boys and girls and men and women are equally protected across ages.